Effectiveness Analysis Of Applications Netsupport School 10 Based Iso / Iec 9126-4 Metrics Effectiveness - Ahmad Cucus; Nelcy Novelia (Bandar Lampung University (UBL), 2013)
Along with the development of technology in this era of globalization, many organizations and educational world that requires increasingly sophisticated technology and assist in employment and education today, One technology that is helpful in the world of education is NetSupport School 10 technologies that can help teachers to monitor students' computer time lessons. NetSupport Discovered by a group called NetSupport Limited or now called NetSupport Inc.. based in peterborough English in 1989. Analysis Monitoring System NetSupport School 10 was conducted to determine whether this software has been effective in its use in accordance with Standard ISO / IEC 9126-4 Effectiveness Metrics and targets expected by the users, To find out more the effectiveness of NetSupport School 10 authors will describe the calculation of the level of effectiveness using metrics-metrics that exist in ISO / IEC 9126-4 Effectiveness Metrics.